Woven hybrid Biocomposite: Mechanical properties of woven kenaf bast fibre/oil palm empty fruit bunches hybrid reinforced poly hydroxybutyrate biocomposite as non-structural building materials - Khoshnava, S.; Rostami, R.; Ismail, Mohamed; Rahmat, A.; Ogunbode, B. (Elsevier BV, 2017)
© 2017 Green or Biocomposite materials encompass biopolymers and natural fibers (NFs) from renewable resources, which is helped to eliminate non-renewable waste, reduce raw material usage, and lessen greenhouse gas emissions. This paper aimed to assess and develop specific biocomposite in terms of mechanical properties, which prepared by lamination and compression molding method. The woven kenaf bast fibre (KBFw) is deliberated as reinforcement in this study due to the high tensile strength which was hybridized with oil palm empty fruit bunches (EFB) due to high toughness of EFB for covering the impact properties of biocomposite. The polyhydroxybutyrate (PHB) is a common biodegradable polymer that is targeted as matrix for green composite. The triethyl citrate (TEC) was chosen as plasticizer for improving flexibility and handling of PHB films. The scanning electron microscope was used to understand and investigate the tensile-fractured surface of different hybrid biocomposite. The results show that the tensile and flexural properties would be increase when NFs with higher tensile strength was used as skin fibre in term of hybrid composite. Conclusively, the flexural stiffness of biocomposite increase when the KBFw PHB biocomposite is hybrid with FEB reinforcement. The tensile and flexural test of KBFw/EFB hybrid reinforced PHB biocomposite with 11 layers (sample E) is determined that sample E has capability to replace with some wood and woody production.